Analisis Strategi Manajemen Sumber Daya Manusia Polri Dalam Mengelola Keterbatasan Personil Pada Jabatan Perwira Di Polres Kubu Raya Polda Kalimantan Barat - Teuku Rivanda Ikhsan; Pantius Drahen Soeling (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The National Police of the Republic of Indonesia is a state instrument that plays a role in maintaining public order and security, providing protection, protection and service to the community, as well as carrying out law enforcement, in the context of maintaining domestic security. To support the implementation of this role, quality Polri human resources are needed in every position or function. The limitation of personnel is one of the obstacles that currently must be faced by the National Police, especially the Kubu Raya  District Police in preparing an optimal work composition. One of them is the lack of personnel with the rank of first officer which is the first line supervisor in controlling the personnel on duty. This research is a qualitative research that describes the HR management strategy of the National Police, especially in succession planning in managing the limitations of first officer rank personnel that are currently still occurring at the Kubu Raya District Police. The implementation of an appropriate HR management strategy is expected to be able to solve these problems, so that it is expected to be able to realize an increasingly prime Polri posture in providing services to the community.